ANALISIS EKONOMI RUMAH TANGGA PETANI SEKALIGUS PETERNAK (Studi Kasus: Desa Pujon Kidul Kecamatan Pujon Kabupaten Malang) Analysis Of Household Economic Farmers at Once Breeders (Case Study: Pujon Kidul Village, Pujon District, Malang Regency) - jumaidah jumaidah; Farida Syakir; Bambang Siswadi (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
ABSTRACTIncreased income of farmer households determines family welfare and economic characteristics of farmer households as well as farmers in Pujon Kidul Village, Pujon District, Malang Regency. The aim of this study to find out income and R/C ratio for farming tomatoes and dairy cows and the largest contribution income from farm households between farming tomatoes and dairy cows. The survey method used in this study by sampling using a random method (simple random sampling) on 29 farmers and respondent farmers. The analytical method used is R/C ratio and 2SLS (Two Stage Least Square) methods to estimate the parameters simultaneous economic income of tomato farmer households. The results of the study show that farmers' household economic income parameters from tomato farming can contribute 49 percent to the economic income of farm households with an R/C ratio 3,13. While cow's milk business is able to contribute 51 percent of the household economic income of farmers with an R/C ratio 1,96. Tomato farming is significantly affected by tomato production, tomato prices, business costs, and labor. While cow's milk business is influenced significantly by the number of cows, cattle feed costs, and labor. In tomato production is significantly affected by land area and number of seeds. Key words: income parameter, contribution, household economy.